Humour at the workplace: Leader’s humour and employee’s trust in the leader - Robinson, J. (University of Jaffna, 2020)
Humour at the workplace has become an exciting area of research in organizational behavior and management. There is a lack of studies on the influence of the leader’s humour on employee trust, particularly in the Sri Lankan context. This study aims to examine the impact of leaders’ styles of humour (affiliate, self-enhancing, aggressive self-defeating) and its impact on employees’ trust in their leader. The researcher adopted a quantitative approach to conduct this study. This study was conducted with 202 employees from public sector organizations. A convenience sampling method was adopted to recruit respondents. The proposed model was assessed by hierarchical multiple regression. Four personal and demographic variables were controlled in this study. This study indicated that the control variable has no significant influence on employee trust in their leader. Affiliate and self-defeating style of humour had a positive and negative influence on trust, respectively, as proposed. Nevertheless, unexpectedly self-enhancing and aggressive styles of humour had no significant influence on trust in the leader. This study contributes to the literature by investigating the influence of leaders' four humour styles on subordinate’s trust in their leaders in a new, Sri Lankan cultural context. This study contributes to the management practice by identifying humour style that positively and negatively influences subordinates’ trust in the Sri Lankan context. This study suggests that leaders can use more affiliate humour to create a positive work environment and enhance their subordinates’ trust. Leaders are advised to avoid aggressive self-defeating humour in the workplace. Further studies need to be conducted with Moderator (e.g. gender) and mediator variable (e.g. emotions) to deepen the understanding of humor's influence on employees' work behaviour in Sri Lankan cultural context.
Keywords: culture; humor; leadership; Sri Lanka; trust